"I Am Super Straight and I Prefer You be Too": Constructions of Heterosexual Masculinity in Online Personal Ads for "Straight" Men Seeking Sex With Men. (July 2015) - Reynolds, Chelsea
The theory of online disembodiment, which suggests sexual identity online may be incongruent with real-life self-presentation, is problematized by new dating technologies that may lead to meeting in real life (IRL). Expectations for a single "authentic" sexual identity increase with the likelihood of meeting IRL. This study examines sexual scripting and social constructions of heterosexual masculinity among "straight" men seeking homosexual sex on Craigslist personal ad forums in five U.S. cities. I argue that heterosexual masculinity is enacted by "straight" men who seek sex with men on Craigslist to reinforce authentic heterosexuality among audiences of "out" gay men posting in the same forums.